Teaching Children with Learning Disabilities: Exploring the Challenges of Regular Teachers in Anambra State - Nwankpa, Favour Chiamaka; Nwosu, Kingsley Chinaza (Journal of Research in Industrial Technology and Educational Studies, 2025)
This study explored the challenges regular primary school teachers face as they teach children with learning disabilities in Awka, Anambra State. Phenomenological research design was employed in the study, and 15 teachers who teach pupils with learning disabilities were purposively sampled. Data were obtained through face-to-face interviews and analyzed using thematic content analysis. Findings revealed that four themes emerged: teaching and learning related challenges, behavioural and attitudinal challenges, instructional and structural challenges, and parental/home-related challenges. It was concluded that regular primary school teachers faced notable instructional, behavioural, structural, and collaborative difficulties when teaching pupils with LDs. Recommendations were made.